The relationship between domestic credit and income: Evidence from Latin America - (:unkn) unknown (My University, 2013)
In this paper, we examine the relationship between the domestic credit by banking sector and Gross Domestic Product (GDP) per capita in the balanced panel framework of 20 Latin America countries from 1960 to 2010. Panel Cointegration tests of Kao (1999), Maddala and Wu (1999) and Westerlund (2006, 2007) suggest that there is a significant long-run relationship between the domestic credit and the GDP per capita in Latin America countries. Furthermore, results from panel causality tests indicate that there is a unidirectional causation which runs from domestic credit to the GDP per capita.
Keywords: Domestic Credit; Income; Latin America; Panel Causality; Panel Cointegration